MYC prevents apoptosis and enhances endoreduplication induced by paclitaxel. - Giuliana Gatti (Public Library of Science (PLoS), 2009)
Background The role of the MYC oncogene in the apoptotic pathways is not fully understood. MYC has been reported to protect cells from apoptosis activation but also to sensitize cells to apoptotic stimuli. We have previously demonstrated that the down-regulation of Myc protein activates apoptosis in melanoma cells and increases the susceptibility of cells to various antitumoral treatments. Beyond the well-known role in the G1-->S transition, MYC is also involved in the G2-M cell cycle phases regulation. Methodology/principal findings In this study we have investigated how MYC could influence cell survival signalling during G2 and M phases. We used the microtubules damaging agent paclitaxel (PTX), to arrest the cells in the M phase, in a p53 mutated melanoma cell line with modulated Myc level and activity. An overexpression of Myc protein is able to increase endoreduplication favoring the survival of cells exposed to antimitotic poisoning. The PTX-induced endoreduplication is associated in Myc overexpressing cells with a reduced expression of MAD2, essential component of the molecular core of the spindle assembly checkpoint (SAC), indicating an impairment of this checkpoint. In addition, for the first time we have localized Myc protein at the spindle poles (centrosomes) during pro-metaphase in different cell lines. Conclusions The presence of Myc at the poles during the prometaphase could be necessary for the Myc-mediated attenuation of the SAC and the subsequent induction of endoreduplication. In addition, our data strongly suggest that the use of taxane in antitumor therapeutic strategies should be rationally based on the molecular profile of the individual tumor by specifically analyzing Myc expression levels.